Cost variation analysis of statins available in India - Gopalakrishna, Ashika Arka; Bose, Noah M.; Stanly, Sharon M. (International Journal of Basic & Clinical Pharmacology, 2021)
Background: The current study aimed to find out the percentage cost variation among the various brands of statins marketed in India. Statins are HMG-CoA reductase inhibitors which are widely prescribed as blood cholesterol lowering agents and hence reduce illness and mortality in those who are at high risk of cardiovascular disease. There are numerous brands of statins are marketed in India. Methods: Cost of a particular drug manufactured by different companies in the same strength and the dosage form was obtained from the price list provided by the pharmaceutical companies in current index of medical specialities (CIMS) (42nd year January to April 2021). The difference in the maximum and the minimum price of the same drug manufactured by different pharmaceutical companies, cost ratio and the percentage variation in price were analysed. Results: The percentage cost variation of statins was seen highest with tablet atorvastatin 20 mg (564.06%), followed by combination of capsule atorvastatin 10 mg+aspirin 75 mg (325%) which was followed by combination of film coated tablet atorvastatin 10 mg+fenofibrate 160 mg (267.4%), tablet rosuvastatin 20 mg (171.1%), tablet lovastatin 10 mg (108.9%), combination of tablet rosuvastatin 10 mg+fenofibrate 160 mg (87.34%) and lowest was seen with tablet simvastatin 20 mg (6.0%). Conclusions: There is a very wide cost variation among different brands of statins marketed in India. The percentage cost variation was found to be the highest among the moderate intensity statins.